PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA QUIZIZZ DAN MINAT BELAJAR TERHADAP LITERASI IPA PADA MATERI PENYERAPAN AIR PADA TUMBUHAN DI KELAS IX SMP NEGERI 1 GOME KABUPATEN PUNCAK (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Discovery Learning model assisted by Quizizz media compared to conventional Discovery Learning and the effect of learning interest on science literacy in the digestive system material of grade IX students of SMP Negeri 1 Gome, Puncak Regency, while also testing the interaction between the two. The method used was a quasi-experimental with a 2 × 2 factorial design, involving samples selected through cluster random sampling into two groups, namely the experimental class assisted by Quizizz and the conventional control class. The research instruments were a multiple-choice science literacy test that had been validated and reliable and a Likert scale learning interest questionnaire. Data were collected through tests and questionnaires, then analyzed using a two-way ANOVA test with the help of SPSS 26. The results showed that there was a significant effect of the learning model on science literacy (Sig. = 0.000 < 0.05), a significant effect of learning interest on science literacy (Sig. = 0.014 < 0.05), and a significant interaction between the learning model and learning interest (Sig. = 0.026 < 0.05). These findings confirm that Quizizz-assisted Discovery Learning is more effective in improving science literacy, that learning interest contributes to learning outcomes, and that the combination of the two has a significant influence on students' science literacy achievement.